Laser speckle contrast imaging of perfusion in oncological clinical applications - Hren, Rok (Radiology and oncology (Ljubljana), 2024)
Background. Laser speckle coherence imaging (LSCI) is an emerging imaging modality that enables noninvasive visualization and assessment of tissue perfusion and microcirculation. In this article, we evaluated LSCI in imaging perfusion in clinical oncology through a systematic review of the literature. Methods. The inclusion criterion for the literature search in PubMed, Web of Science and Scopus electronic databases was the use of LSCI in clinical oncology, meaning that all animal, phantom, ex vivo, experimental, research and development, and purely methodological studies were excluded. Results. Thirty-six articles met the inclusion criteria. The anatomic locations of the neoplasms in the selected articles were brain (5 articles), breasts (2 articles), endocrine glands (4 articles), skin (12 articles), and the gastrointestinal tract (13 articles). Conclusions. While LSCI is emerging as an appealing imaging modality, it is crucial for more clinical sites to initiate clinical trials. A lack of standardized protocols and interpretation guidelines are posing the most significant challenge.
Keywords: lasersko kontrastno slikanje; onkologija; perfuzija